A Systematic Review of the Literature on Screening for Exercise-Induced Asthma: Considerations for School Nurses. (February 2015) - Worrell, Kelly; Shaw, Michele R.; Postma, Julie; Katz, Janet R.
Asthma is a major cause of illness, missed school days, and hospitalization in children. One type of asthma common in children is exercise-induced asthma (EIA). EIA causes airway narrowing with symptoms of cough and shortness of breath during exercise. The purpose of this article is to review the literature relevant to screening children and adolescents for EIA and to inform development of a school nurse–led EIA screening program. A systematic review of EIA screening tests was conducted by searching PUBMED for key terms. Sixty-seven articles were identified; after review only seven met the inclusion criteria. The most common screening test was the 6-min exercise challenge. School-based screening programs have the potential to identify EIA among undiagnosed children and adolescents. School nurses are health professionals with the knowledge and skills necessary to develop successful screening programs in the school setting. Based on results of the literature review, we present implications for developing screening programs in schools to identify children with undiagnosed EIA.